Impact of Sustainable Biostimulators on Yield and Phytochemical Traits of Bottle Gourd (Lagenaria siceraria L.) - Abd-Allah Gahory; Wagdi Saber Soliman; Rofayda Sayed; Ahmed M. Abbas; Sabri Salaheldin (Horticulturae)
Lagenaria siceraria is a nutritionally and medicinally important crop. Biostimulants offer a sustainable alternative to agrochemicals, yet their effects on bottle gourd remain largely unexplored. This study was conducted over two consecutive seasons (2021 and 2022) under open-field conditions. The aim was to evaluate the impact of eco-friendly biostimulants—salicylic acid (SA), humic acid (HA), and seaweed extract (SW)—on the growth, yield, and phytochemical composition of bottle gourd (Lagenaria siceraria). A randomized complete block design with a factorial arrangement was implemented, including ten treatments with three concentrations of SA, HA, and SW, alongside a control. The results demonstrated that these sustainable growth enhancers significantly improved plant growth parameters. The application of 1.2 g L−1 HA produced the longest plants with the highest leaf and flower number, while fruit traits such as length and diameter were notably enhanced by the 3 mL L−1 SW and 0.8 g L−1 SA treatments. Fruit and seed dry weights were also significantly increased, with the 2 mL L−1 SW and 0.16 g L−1 SA treatments yielding the heaviest fruits, and the 3 mL L−1 SW treatment leading to the highest seed dry weight per fruit. Higher concentrations of SA, HA, and SW, particularly 3 mL L−1 SW, resulted in significant increases in total phenolic content, total flavonoid content, and antioxidant activity. Additionally, biostimulant treatments influenced fixed oil content and composition, with variations in fatty acid profiles. GC analysis identified 21 compounds, with linoleic acid as the dominant fatty acid, reaching its highest concentration under the 1 mL L−1 SW treatment. These findings highlight the potential of sustainable biostimulants in enhancing the productivity and nutritional quality of bottle gourd, supporting the adoption of organic and eco-friendly farming practices in open-field vegetable production.